Impacto da persistência dos sintomas na funcionalidade em casos leves da Covid-19 - Sousa, Barbara Galdino de (2024)
The outbreak of the new coronavirus disease began in 2019 and became pandemic at the beginning of the following year due to the high transmissivity of the virus. Disease that affects several systems of the human body and causes respiratory, cardiovascular and osteomyoneuroarticular complications that affect electrical activities. Eighty percent of patients did not require hospitalization and were classified as mild cases; This population is not exempt from functional repercussions after the acute phase of the disease. The objective of this work was to analyze the impact of the persistence of symptoms on functioning in mild cases of Covid-19 after six months of infection. This is an observational, analytical, exploratory, cross-sectional study, with a quantitative approach to the data. Carried out at the Cardiorespiratory Physiotherapy Laboratory of the Federal University of Ceará, from November 2022 to May 2023 (CAAE: 64780022.1.0000.5054). The sample consisted of 61 individuals who had mild Covid-19, that is, they did not require hospitalization due to the disease, and stated that the symptoms persisted. Sociodemographic, anthropometric and clinical data, including the acute phase and post-Covid symptoms, were assessed using a structured questionnaire. To assess self-perceived health, including functioning, the WHODAS 2.0 (World Health Organization Disability Assessment Schedule 2.0) was used. Functional tests were performed to evaluate respiratory muscle strength and respiratory function (vacuometry and spirometry). The data were analyzed using the IBM SPSS Statistics 21 software. The sample of this study included 61 participants with a mean age of 38.84±12.79 years and 65.6 women, with the most reported persistent symptoms during exercise being dyspnea ( 45.9%), memory loss (44.3%), musculoskeletal pain (14.8%) and hair loss (23%). The level of functioning is lower in those patients who present persistent symptoms (p=0.001). The contextual factors considered in this study were not statistically significantly associated with functioning levels, however, the worst levels of functioning related to cognition were observed in patients from low socioeconomic classes and in those who received government assistance (p=0.009). The strength of the expiratory muscles (65.03±20.12cmH2O) and the peak expiratory flow (60.14±24.92L) demonstrated limits in the respiratory assessment performed, and their transparency with functioning was negative with regard to mobility, domestic services, work and/or college and participation. Factors such as female gender and low weight are related to lower respiratory muscle strength, contributing to reports of dyspnea on exertion. The persistence of symptoms is associated with low levels of functioning, contextual factors such as income and socioeconomic class can favor a negative impact, which is why it is essential for comprehensive care for these patients to understand that these barriers to functioning generate functional and psycho-emotional limitations.